THE NEW UNIVERSITY - NEW TASKS - G. Bogachyova; B. Denisov; I. Matskulyak (Вестник университета)
The scientific concept of development of the joint university is offered. The triad of its functioning is proved: economy, management, law. The particular significance is given to social (humanitarian) sciences in education. The creation of a new of the humanitarian center is offered in the university, a number of its functions is formulated. Some practical offers are suggested.